Uma proposta de sequência didática para o ensino de cinemática utilizando experimentos - Simas, Aristeu Pereira (2021)
The present work is about the report of the production and elaboration of a didactic sequence to be applied in the 9◦ year of elementary school II. A didactic sequence is a set of ordered, structured activities aimed at achieving an educational objective, that is, student learning. In this sequence, we deal with the teaching of kinematics, which is an area of Physics that studies the movements of bodies without caring about the cause of the movement, from the initial part to relative movement. To trigger our proposal, we based this didactic sequence on Lev Vygotsky’s sociocultural theory, as this theory emphasizes the interaction between people in development and the culture where they are inserted. It is important to point out that in this didactic sequence, we emphasize the study of Kinematics using experiments, as they provide advantages when used in the classroom, such as the motivation caused in the student by seeing something different in the classroom and there is a greater student interest in the use of experiments.